2015
DOI: 10.1073/pnas.1505939112
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution in vivo imaging of mouse brain through the intact skull

Abstract: Multiphoton microscopy is the current method of choice for in vivo deep-tissue imaging. The long laser wavelength suffers less scattering, and the 3D-confined excitation permits the use of scattered signal light. However, the imaging depth is still limited because of the complex refractive index distribution of biological tissue, which scrambles the incident light and destroys the optical focus needed for high resolution imaging. Here, we demonstrate a wavefrontshaping scheme that allows clear imaging through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
137
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 46 publications
0
137
0
1
Order By: Relevance
“…A recent study demonstrated that advanced wavefront correction can compensate for high-order aberrations in the mouse skull, thus making it possible to resolve structures on the micron scale within the mouse brain (Park et al, 2015). Although we have not attempted two-photon imaging through our preparation, relatively minor additions to two-photon imaging hardware (a MEMS deformable mirror) may in the future make such experiments feasible.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that advanced wavefront correction can compensate for high-order aberrations in the mouse skull, thus making it possible to resolve structures on the micron scale within the mouse brain (Park et al, 2015). Although we have not attempted two-photon imaging through our preparation, relatively minor additions to two-photon imaging hardware (a MEMS deformable mirror) may in the future make such experiments feasible.…”
Section: Discussionmentioning
confidence: 99%
“…The highspeed operation is required in functional imaging with awake animals and the structural imaging of cellular dynamics, where the motion of the objectives-of-interest may introduce measurement artifacts. As we have demonstrated before [24][25][26]40], IMPACT works well in the ballistic regime for in vivo imaging, and the compensation wavefront can be effective for >60 minutes when imaging mouse cerebral cortex [17]. Further details of the two techniques can be found in our previous work [16,24].…”
Section: Experimental Setup and Principlesmentioning
confidence: 81%
“…Nevertheless, by combining IMPACT and the OPLUL based volumetric imaging, we can record the dynamics within the compensation volume in 3D with improved signal strength and signal-to-background-ratio, which provides a solution for volumetric imaging of biological dynamics at large depth. We expect that the deep tissue volumetric imaging demonstrated here can also be implemented by combining OPLUL with other configurations of wavefront correction, such as the single conjugated adaptive optics [40,[43][44][45][46] which has shown extended compensation field of view. Moreover, IMPACT and OPLUL are both compatible with fluorophores of longer excitation and emission wavelengths in two-photon and three-photon excitation [47], which can further improve the imaging depth.…”
Section: Discussionmentioning
confidence: 99%
“…Reports in both simulation [6][7][8] and experiment [9][10][11][12][13] have demonstrated the FOV advantage of conjugate AO as well as its feasibility. For example, conjugate AO has been applied in scanning microscopy configurations using both one- 9 and twophoton 10,11 microscopy. It has also been applied in widefield (i.e., nonscanning) microscopy configurations with transillumination geometries.…”
Section: Introductionmentioning
confidence: 93%